Investigation of Determinants of Financial Distress in Manufacturing Companies - Mulatsih, Listiana Sri; Dharmawan, Donny; Tumiwa, Ramon Arthur Ferry; Judijanto, Loso; Alfiana, Alfiana (International Journal of Artificial Intelligence Research, 2024)
Financial distress refers to a continuous decline in a company's financial performance, necessitating prediction and mitigation. It typically begins with the company’s inability to meet its short-term obligations, signaling a deterioration in financial condition. This study aims to examine the effects of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on financial distress, with company size serving as a moderating variable. The research employs regression analysis and quantitative methods, focusing on manufacturing firms listed on the Indonesia Stock Exchange that consistently published financial reports from 2020 to 2023. Using purposive sampling, the study selected 40 samples from 10 companies, with data analyzed through Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that ROA significantly impacts financial distress, while CR and DER have no such effect during the observed period. Furthermore, company size moderates the relationship between ROA and CR with financial distress but does not moderate the influence of DER on financial distress. These results provide managerial implications, serving as indicators for corrective actions to prevent financial distress or potential bankruptcy in manufacturing companies